2022
DOI: 10.3390/math10142381
|View full text |Cite
|
Sign up to set email alerts
|

One Aggregated Approach in Multidisciplinary Based Modeling to Predict Further Students’ Education

Abstract: In this paper, one multidisciplinary-applicable aggregated model has been proposed and verified. This model uses traditional techniques, on the one hand, and algorithms of machine learning as modern techniques, on the other hand, throughout the determination process of the relevance of model attributes for solving any problems of multicriteria decision. The main goal of this model is to take advantage of both approaches and lead to better results than when the techniques are used alone. In addition, the propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Namely, the required time for its execution, which is evidently longer than the time required if only one of the algorithms aggregated in the proposed ensemble was used, is not a limitation for working in real time, which is valid for considered problem. of human life, such as traffic and education, which were also considered as problems in the literature [101,102].…”
Section: Discussionmentioning
confidence: 99%
“…Namely, the required time for its execution, which is evidently longer than the time required if only one of the algorithms aggregated in the proposed ensemble was used, is not a limitation for working in real time, which is valid for considered problem. of human life, such as traffic and education, which were also considered as problems in the literature [101,102].…”
Section: Discussionmentioning
confidence: 99%
“…From other site from planed research in technique and methodology for solving considered healthcare problem and problems in healthcare which already was subject of research of authors [114,115] authors will deal in feature with other from many different problems in healthcare and other fields of human life as for example traffic and education which the authors have already done [116,117].…”
Section: Discussionmentioning
confidence: 99%
“…By acting as an early warning system, these predictive models enable the implementation of focused support measures and intervention techniques to enhance student learning outcomes [1]. Machine learning algorithms and data mining techniques are commonly utilized in student performance prediction modeling [2]. These techniques analyze various attributes such as grades, educational background, psychological evaluation, and demographics to generate predictions about a student's future performance [3].…”
Section: Introductionmentioning
confidence: 99%
“…They showed that their technique can improve the performance of student performance prediction models. Ranđelović et al [2] proposed a multidisciplinary-applicable aggregated model based on analytic hierarchy process and ReliefF classifier to predict further students' education. Xu et al [8] introduced a two-layer machine learning architecture consisting of multiple base predictors and a set of ensemble classifiers to predict student performance in degree programs.…”
Section: Introductionmentioning
confidence: 99%